Peran Media Sosial dalam Pembentukan Identitas Sosial Siswa SMP Di Era Digital - Kristina Marta Noviance; CarCarolus Borromeus Mulyatno (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
This research aims to analyze the role of social media in shaping the social identity of junior high school students in the digital era. Social media has become an integral part of adolescents' lives, where they use platforms such as Instagram, TikTok, and WhatsApp to interact and construct self-images. The interaction processes on social media influence how students perceive themselves and how they are perceived by others. This study employs a qualitative approach, using interviews and observations to identify factors influencing the formation of students' social identity. The findings reveal that social media plays a significant role in both reinforcing and altering students' social identity through various forms of social interaction, including the creation and acceptance of group norms. The positive and negative impacts of social media usage on students' social and emotional development are also discussed in this research.AbstrakPenelitian ini bertujuan untuk menganalisis peran media sosial dalam pembentukan identitas sosial siswa SMP di era digital. Media sosial telah menjadi bagian penting dari kehidupan remaja, di mana mereka menggunakan platform seperti Instagram, TikTok, dan WhatsApp untuk berinteraksi dan membangun citra diri. Proses interaksi di media sosial mempengaruhi bagaimana siswa memandang diri mereka sendiri serta bagaimana mereka dipandang oleh orang lain. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara dan observasi untuk mengidentifikasi faktor-faktor yang mempengaruhi pembentukan identitas sosial siswa. Hasil penelitian menunjukkan bahwa media sosial berperan signifikan dalam memperkuat maupun mengubah identitas sosial siswa melalui berbagai bentuk interaksi sosial, termasuk penciptaan dan penerimaan norma-norma kelompok. Dampak positif dan negatif dari penggunaan media sosial terhadap perkembangan sosial dan emosional siswa juga dibahas dalam penelitian ini.